Modeling ways of improving Green economy and environmental protection in the context of governance - Pyliavskyi, Iulii; Martusenko, Iryna; Molnar, Oleksandr; Dzyana, Halyna; Kushniriuk, Voolodymyr (Business: Theory and Practice, 2021)
Today, the principles of a green economy are being updated and studied not only by experts in the field of environmental economics, but also in various political circles. A large number of countries use different instruments and principles of a green economy in their development policies and strategies. However, some countries fear this transformation because they believe that the transition to a green economy model may hinder their development. Thus, the formation of a clear methodology for the “green” economy is extremely relevant today. The main purpose of the study is to form ways to improve green economy and environmental protection in the context of governance. The article discusses the prerequisites for implementation, the basic principles of Green economy into the system of public administration, and also provides a system for modelling ways to implement the principles of Green economy using the IDEF0 methodology. This methodology allows to clearly seeing the ways and means of achieving this goal.